2006
DOI: 10.1080/10715760600632552
|View full text |Cite
|
Sign up to set email alerts
|

Turning point in apoptosis/necrosis induced by hydrogen peroxide

Abstract: The turning point between apoptosis and necrosis induced by hydrogen peroxide (H2O2) have been investigated using human T-lymphoma Jurkat cells. Cells treated with 50 microM H2O2 exhibited caspase-9 and caspase-3 activation, finally leading to apoptotic cell death. Treatment with 500 microM H2O2 did not exhibit caspase activation and changed the mode of death to necrosis. On the other hand, the release of cytochrome c from the mitochondria was observed under both conditions. Treatment with 500 microM H2O2, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(122 citation statements)
references
References 37 publications
7
113
0
2
Order By: Relevance
“…H2O2 and heat shock are alternative treatments to induce tumour cell death. Hydrogen peroxide induces apoptosis via the caspase activation or necrosis by decreasing intracellular adenosine triphosphate (ATP) [30], while heat shock is known to favour HSP70 expression, a molecule involved in DC maturation and cross-presentation [10,[31][32][33][34]. Our results show that H2O2 plus heat shock succeeded in inducing necrosis of RCC cells.…”
Section: Discussionsupporting
confidence: 49%
“…H2O2 and heat shock are alternative treatments to induce tumour cell death. Hydrogen peroxide induces apoptosis via the caspase activation or necrosis by decreasing intracellular adenosine triphosphate (ATP) [30], while heat shock is known to favour HSP70 expression, a molecule involved in DC maturation and cross-presentation [10,[31][32][33][34]. Our results show that H2O2 plus heat shock succeeded in inducing necrosis of RCC cells.…”
Section: Discussionsupporting
confidence: 49%
“…A great deal of emerging evidence suggests that ROS are crucial mediators in intracellular signaling, including the Toll-like receptor signaling pathway, and ROS scavenging or NOX inhibition suppresses LPS-induced cytokine production (Bonizzi et al, 1999;Davies et al, 1999;Lee et al, 1999;Aslan et al, 2003;Tonks et al, 2005;Nakahira et al, 2006;Saito et al, 2006). However, the sources of ROS after the administration of these stimuli remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the NADPH-oxidases (NOX) and cyclooxygenases / lipoxygenases are generally recognized as the principal physiological sources of O2 -, which is in turn dismutated into H2O2 (Babior et al, 1999;Griendling et al, 1999;Van Heerebeek et al, 2002;Kuhn et al, 1999;Rhee et al, 2003). H2O2 is now generally believed to be one of the most important ROS molecules in the modulation of multiple cellular events, including receptor-mediated signaling, apoptosis, proinflammation, and metabolism (Davies et al, 1999;Lee et al, 1999;Aslan et al, 2003;Tonks et al, 2005;Saito et al, 2006). Although the sources of ROS generated after stimulation with proinflammatory cytokines such as TNF-α and IL-1β remain to be clearly elucidated, several reports have indicated that 5-lipoxygenase (5-LOX) activity may be critically related to intracellular ROS production (Los et al, 1995;Lee et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Vertical bars represent the means±SE ( n =6). * Signifi cant differences ( P <0.05) and ** highly signifi cant differences ( P <0.01 (Saito et al, 2006). Relatively higher GPx activity might lead to lower GSH levels in the 5 μg/L Cd…”
Section: Discussionmentioning
confidence: 99%
“…-groups compared with that in 50 μg/L Cd 2+ -groups (Saito et al, 2006), which could explain the relatively higher sHsps in the 50 μg/L Cd-groups (Kannan et al, 2001). In addition, this phenomenon was in line with the inverted U-shaped model (a low dose of stimulation and high dose of inhibition) in toxicology (Calabrese, 2003;Calabrese, 2004 …”
Section: +mentioning
confidence: 96%